2014
DOI: 10.1111/pme.12455
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Incurred in the Exclusion of Vascular Filling in Transforaminal Epidural Steroid Injections: Fluoroscopy, Digital Subtraction Angiography, and CT/Fluoroscopy

Abstract: The use of DSA imaging to exclude vascular uptake during TFESI increases radiation dose over CF. CT/F incurs additional dose beyond most DSA. Minimizing radiation dose by limiting DSA and CT/F use to spine segments or clinical situations involving higher risk may be desirable. However, the incremental radiation doses incurred by DSA or CT/F are of such low magnitude that health risks cannot currently be estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In addition, DSA has disadvantages, such as additional radiation exposure to physicians and patients and the high cost of the new and upgraded fluoroscopic equipment (15). DSA was reported to increase the effective radiation dose incurred by 2.3 ~ 4.3 fold for TFEI compared to conventional fluoroscopy (23).…”
Section: E185mentioning
confidence: 99%
“…In addition, DSA has disadvantages, such as additional radiation exposure to physicians and patients and the high cost of the new and upgraded fluoroscopic equipment (15). DSA was reported to increase the effective radiation dose incurred by 2.3 ~ 4.3 fold for TFEI compared to conventional fluoroscopy (23).…”
Section: E185mentioning
confidence: 99%
“…Third, as previously reported in the neurointerventional literature, DSA is associated with significant radiation exposure [19,20]. Maus et al have shown that during transforaminal epidural steroid injections, DSA delivered approximately 2-4-fold more radiation than conventional fluoroscopy during a 5s exposure [21]. A limitation inherent to both CDM and DSM is the use of planar rather than cross-sectional imaging.…”
Section: Discussionmentioning
confidence: 93%
“…In order to minimize the potential for an inadvertent vascular injection during lumbar TFESI, a test dose of contrast medium is recommended before any other agent is injected [3]. Digital subtraction imaging (DSI) has been found to increase the detection of intravascular uptake of contrast compared to live fluoroscopy alone [4,5], but DSI may not be readily available and does increase radiation exposure to both patients and providers [6]. Real time fluoroscopy has been shown to be superior to aspiration tests and static fluoroscopic images [7].…”
Section: N T E R V E N T I O N S O C I E T Ymentioning
confidence: 99%